Chromosome-level genome assembly of Parotis chlorochroalis (Lepidoptera: Crambidae: Spilomelinae) - Mei Xiong; Rui Cheng; Bo He; Chun-Sheng Wu; Chao-Dong Zhu; Arong Luo; Qing-Song Zhou (Scientific Data)
Abstract Parotis Hübner, 1831 is a genus within the family Crambidae, which is recognized as one of the most diverse families of Lepidoptera. Species within the genus Parotis can be readily distinguished from other closely related genera by their distinctive green or yellow-green body coloration. However, the genus Parotis has received relatively limited research attention, and the scarcity of genome-wide molecular resources has impeded a more comprehensive understanding of its evolution, adaptation, and phylogenetic relationships. This study reports the first genome assembly for Parotis chlorochroalis (Hampson, 1912), generated through PacBio Hi-Fi and Hi-C sequencing technologies. The assembled genome has a size of 456.23 Mb, comprising 31 chromosomes. Approximately 181.82 Mb, which constitutes 39.85% of the genome, has been identified as repetitive sequences. The genome assembly includes 16,299 protein-coding genes, of which 94.82% have been functionally annotated. This chromosome-level genome assembly not only advance understanding of P. chlorochroalis but also has the potential to facilitate genomic studies of other lepidopteran species.